DEVELOPING COURSES IN THE BEHAVIOURAL AND SOCIAL SCIENCES FOR MEDICAL STUDENTS: NEW PROSPECTS FOR AN OLD PROBLEM - Peter J.Blizard Peter J.Blizard (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1976)
This paper described methods which can be used to construct